Cardiac alterations following experimental hip fracture - inflammaging as independent risk factor - Lackner, Ina; Weber, Birte; Pressmar, Jochen; Odwarka, Anna; Lam, Charles; Haffner-Luntzer, Melanie; Marcucio, Ralph; Miclau, Theodore; Kalbitz, Miriam (Frontiers in Immunology, 2022)
Background: Cardiac injuries following trauma are associated with a worse clinical outcome. So-called trauma-induced secondary cardiac injuries have been recently described after experimental long bone fracture even in absence of direct heart damage. With the progressive aging of our society, the number of elderly trauma victims rises and therefore the incidence of hip fractures increases. Hip fractures were previously shown to be associated with adverse cardiac events in elderly individuals, which have mainly been attributed to pre-conditioned cardiac diseases. The aim of the present study was to investigate the effect of hip fractures on the heart in healthy young and middle-aged mice. Materials and Methods: Young (12-week-old) and middle-aged (52-week-old) female C57BL/6 mice either received an intramedullary stabilized proximal femur fracture or sham treatment. The observation time points included 6 and 24 h. Systemic levels of pro-inflammatory mediators as well as local inflammation and alterations in myocardial structure, metabolism and calcium homeostasis in left ventricular tissue was analyzed following hip fracture by multiplex analysis, RT-qPCR and immunohistochemistry. Results: After hip fracture young and middle-aged mice showed increased systemic IL-6 and KC levels, which were significantly elevated in the middle-aged animals. Furthermore, the middle-aged mice showed enhanced myocardial expression of HMGB1, TLR2/4, TNF, IL1 and NLRP3 as well as considerable alterations in the myocardial expression of glucose- and fatty acid transporters (HFABP, GLUT4), calcium homeostasis proteins (SERCA) and cardiac structure proteins (desmin, troponin I) compared to the young animals following hip fracture. Conclusion: Young and middle-aged mice showed local myocardial alterations, which might predispose for the development of secondary cardiac injury following hip fracture. Age and the age-associated phenomenon of ‘inflammaging’ seemed to be an independent risk factor aggravating and accelerating cardiac alterations following hip fracture.